Financial Management Education in Traditional Cake Entrepreneurship Under The Share of The Diamond Cooperative in Pisangan Village, South Tangerang - Tri Siswantini; Ayunita Ajengtyas Saputri; Rahmasari Fahria; Sufyati HS (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The main problem in Small, Micro, and Medium Enterprises (MSMEs), one of which is limited capital. Difficulties in obtaining loans or other external capital are partly because MSMEs do not have financial information that is accountable, transparent, has integrity, and is in accordance with Financial Accounting Standards. Apart from that, business financial management is still mixed with household finances, and the lack of knowledge regarding product cost calculations means that MSME products often have higher prices compared to imported products. Community service activities are carried out in collaboration with the Berlian Cooperative in the South Tangerang Region which is engaged in savings and loans and selling traditional Betawi cakes. The aim of this community service (PKM) is to provide education regarding business financial management and mechanisms for calculating costs and product selling prices based on cost accounting. The implementation method is in the form of lectures and simulations of calculating product costs and recording simple financial reports. The results of PKM activities show that the results of questionnaires distributed at the pre-activity stage show that this MSME group still has problems related to business bookkeeping and proper financial management so the average MSME actor in this group still does not know the exact amount of income and costs, and the profits generated from their efforts. Based on this, it is necessary to carry out further training and assistance related to financial management and literacy in banking and non-banking financial services so that MSME players can develop their businesses. Keywords: MSMEs, Financial Governance, Production Costs, Selling Prices